Costa Rica: Estimating the Non-accelerating Inflation Rate of Unemployment - Álvarez Corrales, Cristian (2019)
In this paper we present estimations of the Non-accelerating Inflation Rate of Unemployment or NAIRU for the Costa Rican economy. We highlight the following results: The NAIRU displays an upward trend since the early 90s which was accentuated after the Great Recession when the Costa Rican inflation rate exhibits historically low levels; the estimations of the unemployment gap (the difference between the observed unemployment rate and the NAIRU) indicates that this gap was negative in the nineties and the first half of 2000’s but became positive afterwards. At the second quarter of 2017, the different estimates of the unemployment gap coincide in pointing out that this gap was closed, indicating the absence of aggregate demand pressures. In addition, since 2004, there has been a strengthening in the relationship between inflation and the unemployment gap.